Ultrasound examination of various dental materials and foreign bodies - Hakan Eren; Rüya Sessiz; Yeşim Deniz (Ankara University, 2023)
Purpose To provide information on the sonographic properties of different foreign bodies and dental materials to help with diagnosis. Materials amp; Methods The investigation contained 10 various dental materials and foreign bodies that were consisting of composite, glass ionomer cement, gutta percha, suture, wooden, stone, canal file, acrylic, alginate, and silicone impression material. The objects were embedded to chicken meat and imaged using ultrasonography (USG). Their visibility and posterior acoustic behaviors were evaluated by both hockey and linear transducers. The actual sizes of this objects and measured dimensions by transducers were compared. Results Only gutta percha could not be distinguished in chicken meat. No difference was observed between the measurements made with the hockey and linear transducers and the actual size. Conclusion USG is a useful method for detecting and measuring foreign bodies and dental materials in soft tissues.